Deputation to Lord Halifax : inter-departmental correspondence - McDonald, Florence
017a-0073-001 I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From F. McDonald. To Mr. W. Bolton. Department Secretary's. Date 8th April, 1938. DEPUTATION TO LORD HALIFAX. Sir Walter would like you to send the attached copy of the report of the Deputation to Lord Halifax to members of the General Council. He has amended it and marked it Strictly Private & Confidential. In a covering note to them he would like you to say the following: The interview was fixed up at very short notice, and it was in consequence of the telegram we had received from the Spanish Trade Unions. I communicated with all the members if the F.& G.P.C., and they agreed it was desirable, in view of the telegram, to approach the Foreign Secretary. 292/946/17a/73